2011
DOI: 10.1073/pnas.1109988108
|View full text |Cite
|
Sign up to set email alerts
|

A homolog of male sex-determining factor SRY cooperates with a transposon-derived CENP-B protein to control sex-specific directed recombination

Abstract: Schizosaccharomyces pombe cells switch mating type by replacing genetic information at the expressed mat1 locus with sequences copied from mat2-P or mat3-M silent donor loci. The choice of donor locus is dictated by cell type, such that mat2 is the preferred donor in M cells and mat3 is the preferred donor in P cells. Donor choice involves a recombination-promoting complex (RPC) containing Swi2 and Swi5. In P cells, the RPC localizes to a specific DNA element located adjacent to mat3, but in M cells it spreads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 52 publications
(82 reference statements)
2
24
1
Order By: Relevance
“…The fission yeast CENP-Bs participate in several DNA-directed processes, including transcription, DNA replication, and recombination (1,9,35,37,72). Extensive occupancy of Abp1 and Cbh1 at diverse genetic elements throughout the fission yeast genome supports these multifaceted roles for CENP-Bs (9, 72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fission yeast CENP-Bs participate in several DNA-directed processes, including transcription, DNA replication, and recombination (1,9,35,37,72). Extensive occupancy of Abp1 and Cbh1 at diverse genetic elements throughout the fission yeast genome supports these multifaceted roles for CENP-Bs (9, 72).…”
Section: Discussionmentioning
confidence: 99%
“…CENP-Bbound LTRs could act as versatile regulatory modules, exerting transcriptional control of nearby genes (9,58) and affecting other DNA transactions, such as stabilizing DNA replication forks under certain genomic contexts (72). CENP-Bs also localize to non-LTR-associated promoters and regulate expression of associated genes, several of which are involved in sex-specific directed recombination (37). Most intriguingly, CENP-Bs contribute to the clustering of dispersed Tf2 elements into distinct Tf bodies (9) and thus play a role in genome organization.…”
mentioning
confidence: 99%
“…The Mc binding to this putative promoter might activate swi2S transcription. A recent chromatin immunoprecipitation analysis showed that Mc physically interacts with the swi2S promoter region, as predicted here (Matsuda et al 2011). Whether Mc binding depends on the two inverted presumptive recognition sites needs further investigation.…”
Section: A Model For Swi2l and Swi2s Factors Controlling Directionalitymentioning
confidence: 99%
“…While we were preparing this manuscript for publication, it was reported (Matsuda et al 2011) that the Mc and Abp1 genes control the switching recombination directionality, that Mc protein directly binds to the Swi2 gene regulatory region, and that binding requires Abp1. Results of that report are complementary to some parts of our study and support our conclusions.…”
Section: A Model For Swi2l and Swi2s Factors Controlling Directionalitymentioning
confidence: 99%
“…Swi2 binding to the mat region requires the SRE3, and it was proposed that in M cells Swi2 would reach to the mat2 region by spreading from the SRE3 through a heterochromatin region between mat2 and mat3 via physical interaction with Swi6 (54). Two more proteins, Abp1 and Mc, are required for Swi2 binding to the mat2 region, perhaps by promoting Swi2 spreading (56,57,58). The Mc protein, a transcription factor encoded within the M cassette, provides proper distribution of the RPC by positively regulating the expression of swi2 and swi5 genes in M cells (57).…”
mentioning
confidence: 99%